Th40 cells (CD4+CD40+ Tcells) drive a more severe form of Experimental Autoimmune Encephalomyelitis than conventional CD4 T cells - Vaitaitis, Gisela M.; Yussman, Martin G.; Waid, Dan M.; Wagner, David H. (PloS one, 2017)
CD40-CD154 interaction is critically involved in autoimmune diseases, and CD4 T cells play a dominant role in the Experimental Autoimmune Encephalomyelitis (EAE) model of Multiple Sclerosis (MS). CD4 T cells expressing CD40 (Th40) are pathogenic in type I diabetes but have not been evaluated in EAE. We demonstrate here that Th40 cells drive a rapid, more severe EAE disease course than conventional CD4 T cells. Adoptively transferred Th40 cells are present in lesions in the CNS and are associated with wide spread demyelination. Primary Th40 cells from EAE-induced donors adoptively transfer EAE without further in-vitro expansion and without requiring the administration of the EAE induction regimen to the recipient animals. This has not been accomplished with primary, non-TCR-transgenic donor cells previously. If co-injection of Th40 donor cells with Freund's adjuvant (CFA) in the recipient animals is done, the disease course is more severe. The CFA component of the EAE induction regimen causes generalized inflammation, promoting expansion of Th40 cells and infiltration of the CNS, while MOG-antigen shapes the antigen-specific TCR repertoire. Those events are both necessary to precipitate disease. In MS, viral infections or trauma may induce generalized inflammation in susceptible individuals with subsequent disease onset. It will be important to further understand the events leading up to disease onset and to elucidate the contributions of the Th40 T cell subset. Also, evaluating Th40 levels as predictors of disease onset would be highly useful because if either the generalized inflammation event or the TCR-honing can be interrupted, disease onset may be prevented.